The complex restorative treatment for fractures in the distal metaepiphysis of the humerus - Nosivets, Dmytro; Naumenko, Leonid (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
Proceeding from the analysis of clinical results of treating 20 patients with fractures in the distal metaepiphysis of the humerus (type C by AO classification), the authors worked out a program for complex restorative treatment. All the patients underwent an operation of combined osteosynthesis within a period from a few hours to two days since the moment of injury. The complex restorative treatment consists of 4 periods: 1st – preoperative, 2nd – an early mobilization of the elbow joint, 3rd – a late mobilization of the elbow joint, and 4th – outpatient restorative treatment. An average follow-up period lasted 38.5 months (from 12 to 48 months). A period of fixation with a rod device for external fixation with a ball hinge averaged 5.5 weeks (from 4 to 6 weeks). According to the Mayo clinic scale, the results were assessed as excellent in 14 patients (70%) and good in 6 (30%) an average score being 95 (from 85 to 100 points).